Formation Of Literary Competence Of A Teacher In The Process Of Organizing Students’ Independent Work (Eurasian Journal of Learning and Academic Teaching, 2025)
A particular challenge in teaching literature lies in correlating the subject course with the learner’s real linguistic experience and the process of acquiring literary knowledge. A teacher of philological disciplines in a higher pedagogical educational institution develops professional competence through organizing students’ independent work and applying methods of modern pedagogical technologies.